Advances and Challenges in the Management of Acute Colonic Pseudo-Obstruction (Ogilvie Syndrome) - Jain, Arpana; Vargas, H. David (Clinics in Colon and Rectal Surgery, 2012)
Although acute colonic pseudo-obstruction (ACPO), also known as Ogilvie syndrome, is a well-known clinical entity, in many respects it remains poorly understood and continues to challenge physicians and surgeons alike. Our understanding of ACPO continues to evolve and its epidemiology has changed as new conditions have been identified predisposing to ACPO with critical illness providing the common thread among them. A physician must keep ACPO high in the list of differential diagnoses when dealing with the patient experiencing abdominal distention, and one must be prepared to employ and interpret imaging studies to exclude mechanical obstruction. Rapid diagnosis is the key, and institution of conservative measures often will lead to resolution. Fortunately, when this fails pharmacologic intervention with neostigmine often proves effective. However, it is not a panacea: consensus on dosing does not exist, administration techniques vary and may impact efficacy, contraindications limit its use, and persistence and or recurrence of ACPO mandate continued search for additional medical therapies. When medical therapy fails or is contraindicated, endoscopy offers effective intervention with advanced techniques such as decompression tubes or percutaneous endoscopic cecostomy providing effective results. Operative intervention remains the treatment of last resort; surgical outcomes are associated with significant morbidity and mortality. Therefore, a surgeon should be aware of all options for decompression—conservative, pharmacologic, and endoscopic—and use them in best combination to the advantage of patients who often suffer from significant concurrent illnesses making them poor operative candidates.
Keywords: acute colonic pseudo-obstruction; ogilvie syndrome